Mechanical properties of metal injection molding (MIM) parts - Ji, Chun Hai (2008)
The metal injection molding (MIM) of water-atomized 316L stainless steel powder was carried out in this research. The main objective of this work is to study the effects of MIM processing factors (mainly sintering factors) on the density and mechanical properties of the sintered parts.